Sanitation of citrus germplasm by somatic embryogenesis and shoot-tip grafting - Carimi F.; De Pasquale F.; Fiore S.; D'Onghia A.M. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
Citrus can be infected with several graft-transmissible pathogens, which can be eliminated by the use of in vitro shoot-tip-grafting and by the recently developed technique of somatic embryogenesis from stigma and style culture. An account of the use, advantages and limitations of these sanitation methods is given in order to ensure the movement of healthy citrus genetic resources in appropriate conditions.